(untitled) (Discourse of Law and Administration, 2021)
Changing of Art. 845 of the Code of Civil Procedure, made on January 1, 2019, extended the bailiff ’s powers to examine the ownership status of things in enforcement from movable property. The competence vested in the bailiff constitutes a breach from the systemic position of this authority. So far, the bailiff has not been authorized to make decisions in the area of substantive law. The article discusses the legal nature of the introduced changes. The nature of the evidence on the basis of which the bailiff should determine the ownership status of the property and the effect on the proceedings of determining that the seized thing is not the property of the debtor was indicated. Attention was drawn to the dubious effect of the special regulation of the seizure of movable property for the purposes of the enforcement of maintenance payments. The study analyzes the concept of “clear written evidence” as to the ownership of movable property, assuming that this evidence may only be evidence from an official document. An analysis of the regulation allowing for the enforcement of things belonging to the marital community of property was also carried out, claiming that the introduced change concerns things that were not in the possession of the debtor. Finally, the impact of the changes made on the possible content of the allegations in the complaint on the bailiff ’s activity was discussed.